Using computational modelling to study extensional rheometry tests for inelastic fluids - Aali, Mohammadreza (2021)
The present work focuses on the extensional rheometry test, performed with the Sentmanat extensional rheometer (SER) device, and its main objectives are: (i) to establish the modelling requirements, such as the geometry of the computational domain, initial and boundary conditions, appropriate case setup, and (ii) to investigate the effect of self-induced errors, namely on the sample dimensions and test temperature, on the extensional viscosity obtained through the extensional rheometry tests. The definition of the modelling setup also comprised the selection of the appropriate mesh refinement level to model the process and the conclusion that gravity can be neglected without affecting the numerical predictions. The subsequent study allowed us to conclude that the errors on the sample dimensions have similar effects, originating differences on the extensional viscosity proportional to the induced variations. On the other hand, errors of a similar order of magnitude on the test temperature promote a significant difference in the predicted extensional viscosity.